Studies on Fletcher trait and Fitzgerald trait - Saito, Hidehiko (Thrombosis and Haemostasis, 2010)
The way by which contact of blood with foreign surface accelerates clotting has been elucidated from the discovery of four rare disorders of blood coagulation; Hageman trait, plasma thromboplastin antecedent (PTA) deficiency, Fletcher trait, and Fitzgerald trait. Interestingly, it was unexpectedly found that Fletcher factor is plasma prekallikrein and Fitzgerald factor is high-molecular-weight kininogen; components of the kinin-generating system, thus disclosing intimate relationships among clotting, fibrinolysis and kinin generation which may be viewed as body’s defense reactions against injury. This review mainly reflects our research on Fletcher trait and Fitzgerald trait during the 1970s in Cleveland.
Keywords: Contact factor; kinin system; fibrinolysis; Fletcher trait; Fitzgerald trait